Alimentary system is directly attacked by SARS‐COV‐2 and further prevents immune dysregulation caused by COVID‐19. Issue 4 (31st December 2020) - Chen, Sai; Zhou, Jing; Ou, Xiaoqi; Cheng, Wei; Qin, Yun; Guo, Yingqiang; Jiang, Yunhan
Abstract: Background: SARS‐COV‐2 causes digestive system symptom, the effect of which remains equivocal. Methods: Patients with COVID‐19 were classified into four groups according to symptom. The study traced the onset and duration of symptoms, compared laboratory examinations and conducted bioinformatic analysis. Immune indices were further analysed. Results: By March 16, 25 patients with COVID‐19 and 13 with suspect COVID‐19 were admitted to West China Hospital, Sichuan University. Digestive system symptom group had the highest level of ESR (mm/h, P  < .0001), serum ferritin (ng/ml, P  < .0001), hepatic enzymes ( P  < .05) and retentive lymphocyte count/percentage ( P  < .05) and its subsets ( P  < .05). Combined group (respiratory combined with subsequent digestive system symptom) had the highest level of IL‐6 (pg/ml, P  = .0046), CRP (mg/L, P  = .0004) and moderate lymphocyte depletion. Respiratory system symptom and asymptomatic groups suffered the most from lymphocyte depletion ( P  < .05). Bioinformatic analysis indicated co‐expression of binding related proteins of SARS‐COV‐2 (ACE2, TMPRSS2 and Furin) in small intestine. CD147 was extensively expressed in alimentary tract. CTSL, PIKfyve, TPC2 and CTSB could be detected with ≥moderate expressions in a variety of organs including alimentary system. Conclusions: Alimentary system is possibly attacked by SARS‐COV‐2 other than hyperinflammation or immune dysregulation caused by it. Involvement of alimentary system might further protect mild and moderate cases from lymphocyte depletion caused by COVID‐19.